2017
DOI: 10.1007/s40262-017-0616-3
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacometric Approach to Substitute for a Conventional Dose-Finding Study in Rare Diseases: Example of Phase III Dose Selection for Emicizumab in Hemophilia A

Abstract: BackgroundEmicizumab (ACE910) is a bispecific antibody mimicking the cofactor function of activated coagulation factor VIII. In phase I–I/II studies, emicizumab reduced the bleeding frequency in patients with severe hemophilia A, regardless of the presence of factor VIII inhibitors, at once-weekly subcutaneous doses of 0.3, 1, and 3 mg/kg.MethodsUsing the phase I–I/II study data, population pharmacokinetic and repeated time-to-event (RTTE) modeling were performed to quantitatively characterize the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 47 publications
(50 reference statements)
4
104
1
1
Order By: Relevance
“…Utilizing the phase 1‐1/2 study data, population pharmacokinetic and repeated time‐to‐event (RTTE) modelling were carried out by Yoneyama et al to quantitatively delineate the interrelation between the pharmacometrics of emicizumab and the decrease in bleeding incidence. Simulations were then carried out to examine the minimal exposure anticipated to accomplish zero bleeding episodes for 1 year in at least 50% of patients and to decide the dosing regimens to be examined in phase 3 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing the phase 1‐1/2 study data, population pharmacokinetic and repeated time‐to‐event (RTTE) modelling were carried out by Yoneyama et al to quantitatively delineate the interrelation between the pharmacometrics of emicizumab and the decrease in bleeding incidence. Simulations were then carried out to examine the minimal exposure anticipated to accomplish zero bleeding episodes for 1 year in at least 50% of patients and to decide the dosing regimens to be examined in phase 3 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Phase 3 investigations with the selected dosing regimens are currently under way. Yoneyama further suggested that a pharmacometric method can substitute for a habitual dose‐finding research in rare illnesses and will consolidate the medication development process …”
Section: Resultsmentioning
confidence: 99%
“…18 Large variation was observed in the mean total plasma FVII/ FVIIa levels among rats receiving the same dose of vector genomes/ kg ( Figure 2). However, this does not affect our conclusions as our modelling approach is not limited to prophylactic gene therapy.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Young et al 10 were able to detect a concentration-response relationship of rhFVIIa in only one out of fourteen patients in a multicentre trial evaluating TEG/ROTEM for monitoring efficacy of rhFVIIa. 18 Key benefits of quantifying the relationship between TEG/ROTEM parameters and the probability of having bleeding events may include better monitoring of bleeding risk for patients using a simple laboratory assay and more efficient dose titration of bypassing agents and non-factor products, which ultimately would be of high economic and clinical value. 11,12 The primary efficacy end point in clinical trials of haemophilia is the occurrence of spontaneous bleeding events (event-type data), summarized as annualized bleeding rate (ABR) for statistical evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, they published in 2017 the long‐term extension data of the phase 1/2 study . Satisfied with these early results, Chugai started a novel collaboration with the Big Pharma Roche and Genentech, and developed together a new pharmacometric approach to estimate the optimal dose of emicizumab, thereby avoiding a conventional dose‐finding study and accelerating clinical development. Using the dosing regimen so identified, Genentech, Roche and Chugai decided to perform multinational phase 3 studies (HAVEN 1‐4) that started in 2015.…”
Section: The Role Of Translational Researchmentioning
confidence: 99%